2011
DOI: 10.1038/ng0411-289
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A mutations in acute myeloid leukemia

Abstract: BACKGROUND-The genetic alterations responsible for an adverse outcome in most patients with acute myeloid leukemia (AML) are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 35 publications
(25 reference statements)
1
41
1
Order By: Relevance
“…[15][16][17]19,22 Systematic screening studies found that such mutations do not only occur as sole abnormalities but are often found in combination, probably contributing to the phenotypic heterogeneity found in MDS. 5,25,26 During our search for new molecular lesions associated with MDS, we identified somatic mutations affecting various components of the spliceosomal machinery, similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17]19,22 Systematic screening studies found that such mutations do not only occur as sole abnormalities but are often found in combination, probably contributing to the phenotypic heterogeneity found in MDS. 5,25,26 During our search for new molecular lesions associated with MDS, we identified somatic mutations affecting various components of the spliceosomal machinery, similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The application of high-throughput molecular technologies, including high-density single nucleotide polymorphism arrays (SNP-As) 3 and new sequencing technologies 4,5 has led to the improved characterization of genomic lesions such as chromosomal aberrations and of somatic mutations affecting specific classes of genes, 6 including signal transducers (eg, CBL), [7][8][9][10] apoptotic genes (eg, TP53 and RAS), [11][12][13] genes involved in epigenetic regulation of DNA (eg, DNMT3A, IDH1/2, and TET2), [14][15][16][17][18] and histone modifiers (eg, EZH2, UTX, and ASXL1). [19][20][21][22][23][24] Although some mutations in these factors are activating, most are loss-of-function or hypomorphic mutations and affect bona fide tumor suppressor genes (TSGs).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, accumulating evidence suggests that somatic mutations in DNA methyltransferases and 5mC-modifying enzymes, such as TET proteins, are associated with oncogenic transformation. For instance, mutations in the de novo DNA methyltransferase DNMT3A were recently found in a significant fraction of patients with AML (Shah and Licht 2011;Yan et al 2011).…”
Section: Role Of Tet2 In Hematopoiesis and Leukemiamentioning
confidence: 99%
“…5,11 DNMT3B is considered functionally complementary to DNMT3A with common and differential target specificities, and may be considered to play a role in the aberrant methylation observed in acute leukemia. 12 The mutational screening was performed in some of our pediatric cohort. In particular, 60 T-ALL patients and 90 AML patients were sequenced at the homolog amino acid R823 at exon 23 of DNMT3B and no mutations were found, suggesting that neither methylase provides information about pediatric leukemia at the focused genomic locus.…”
Section: Phf6mentioning
confidence: 99%